Composite Analysis of Home-Based Intervention Studies in Cardiac Disease. Issue 28 (29th October 2015) - Cunningham, Muriel
A composite analysis was conducted of 3 randomized trials of home-based interventions compared with standard care in patients with cardiac disease. Home-based intervention resulted in a shorter hospital stay, better survival, and prolonged days alive and out of the hospital but should be reserved for clinically complex cases to avoid harm.